Health System Barriers and Facilitators to Delivering Additional Vaccines through the National Immunisation Programme in China: A Qualitative Study of Provider and Service-User Perspectives - Dan Gong; Qiyun Jiang; Tracey Chantler; Fiona Yueqian Sun; Jiatong Zou; Jiejie Cheng; Yuqian Chen; Chengyue Li; Mei Sun; Natasha Howard (Vaccines, 2021)
In China, there are two categories of vaccines available from the Chinese Center for Disease Control and associated public health agencies. Extended Program of Immunization (EPI) vaccines are government-funded and non-EPI vaccines are voluntary and paid for out-of-pocket. The government plans to transition some non-EPI vaccines to EPI in the coming years, which may burden public health system capacity, particularly in terms of budget, workforce, supply chains, and information systems. Our study explored vaccinator and caregiver perspectives on introducing non-EPI vaccines into routine immunization and perceived facilitators and barriers affecting this transition. We conducted a qualitative study from a realist perspective, analysing semi-structured interviews with 26 vaccination providers and 160 caregivers in three provinces, selected to represent regional socioeconomic disparities across Eastern, Central, and Western China. Data were analysed thematically, using deductive and inductive coding. Most participants were positive about adding vaccines to the national schedule. Candidate EPI vaccines most frequently recommended by participants were varicella, mumps vaccine, and hand–foot–mouth disease. Providers generally considered existing workspaces, cold-chain equipment, and funding sufficient, but described frontline staffing and vaccine information systems as requiring improvement. This is the first qualitative study to explore interest, barriers, and facilitators related to adding vaccines to China’s national schedule from provider and caregiver perspectives. Findings can inform government efforts to introduce additional vaccines, by including efforts to retain and recruit vaccine programme staff and implement whole-process data management and health information systems that allow unified nationwide data collection and sharing.